Malignant Pleural Effusion: A Contemporary Approach to Diagnosis and Personalized Management - Theresia Rasta Karina; Faisal, Hana Khairina Putri; Elhidsi, Mia (Indonesian Society of Respirology (ISR), 2026)
Malignant pleural effusion (MPE) is a manifestation of advanced malignancy characterized by abnormal accumulation of pleural fluid due to tumor cell infiltration. It most commonly originates from lung, breast cancer, or lymphoma and is associated with dyspnea, chest pain, and impaired quality of life. Diagnosis of MPE is established through pleural fluid cytology or histopathological confirmation, supported by radiological imaging. Liquid biopsy offers a minimally invasive approach for detecting molecular alterations. Although diagnostic and therapeutic modalities have improved, management remains primarily palliative. Therapeutic thoracentesis, chemical pleurodesis using talc, and indwelling pleural catheter (IPC) placement are the main palliative strategies. Combination therapy of IPC with talc slurry demonstrates higher rates of spontaneous pleurodesis and shorter hospital stays. Systemic therapies such as chemotherapy, targeted therapy, and immunotherapy provide additional disease control in selected patients. Although current approaches have improved diagnostic and therapeutic outcomes, most treatments remain palliative. Therefore, a multidisciplinary and personalized strategy is essential to optimize patient quality of life. This review underscores the importance of early diagnosis and management of malignant pleural effusion, including cytology, pleural biopsy, imaging, and liquid biopsy, as well as therapeutic approaches such as thoracentesis, pleurodesis, indwelling pleural catheter, systemic therapy, and palliative care.